Effect of Fluidized Bed Drying, Matrix Constituents and Structure on the Viability of Probiotic Lactobacillus paracasei ATCC 55544 during Storage at 4 °C, 25 °C and 37 °C - Poddar D; Palmer J; Das S; Gaare M; Nag A; Singh H (MDPI (Basel, Switzerland), 2022)
The stabilization of probiotics for application in non-refrigerated food products is a challenging task. In the present study, probiotic Lactobacillus paracasei (Lacticaseibacillus paracasei) ATCC 55544 cells were immobilized in a dairy matrix comprising of whole milk powder, skim milk powder, or milk protein isolate using fluidized bed drying technology. The samples were taken out at different drying stages, with an apparent water activity (aw) of aw 0.5, aw 0.4, and aw 0.3, respectively, and vacuum-packed to maintain the aw and stored at three different temperatures of 4 °C, 25 °C, and 37 °C. The study evaluated the impact of matrix constituents, milk fat, protein, and carbohydrate on the viability of encapsulated probiotic L . paracasei ATCC 55544 during storage for 1 month. The whole milk powder matrix provided superior protection to the bacteria. Confocal Laser Scanning Microscopy (CLSM) was used to investigate the structure of the immobilizing matrix and the location of the probiotic L. paracasei cells embedded within the matrix. The CLSM study revealed that the probiotic bacterial cells are mostly embedded as clusters beneath the top layer. We hypothesize that the biofilm-like structure, together with the protective whole milk powder matrix, helps to retain the superior viability of probiotic cells during storage at non-refrigerated storage conditions of 25 °C and 37 °C.
Keywords: Confocal Laser Scanning Microscopy (CLSM); Lacticaseibacillus paracasei; Lactobacillus paracasei; Scanning Electron Microscopy (SEM); fluidized bed drying; probiotic encapsulation; probiotic storage study; probiotic viability; probiotics; storage temperature; water activity (aw)